IMPLEMENTASI PENGELOLAAN PAJAK BUMI DAN BANGUNAN PERKOTAAN PEDESAAN (PBB-P2) DI KABUPATEN BANDUNG PROVINSI JAWA BARAT - Rosmery Elsye (Jurnal Ilmiah Wahana Bhakti Praja, 2022)
This study aims to determine the extent of the management of PBB-P2, in Bandung Regency, after the enactment of Law 28 of 2009, concerning Regional Taxes and Levies. This study uses a qualitative method, with descriptive analysis, data obtained from primary data and secondary data. The results and conclusions, that PBB-P2 tax management, in Bandung Regency, is carried out by referring to Law 28 of 2009, and tax management guidelines issued by the Directorate General of Taxes, Ministry of Finance, as well as Regent Regulation number: 69 of 2016 concerning the management of PBB-P2 in Bandung Regency. The results where the acceptance of PBB-P2, every year has increased. The Regional Revenue Service which is given the responsibility for tax management, in order to maximize tax revenue, because the Regency area is very large, then formed and established UPTD-UPTD tax services, which have responsibility in its implementation. Each UPTD serves 6 to 7 nearest sub-districts, this is to provide convenience for people who will pay local taxes. And the existence of tax services by using a mobile car, approaching service to the community. So that people feel satisfied with what is done by the Regional Revenue Service of Bandung Regency. Key words: Management, PBB-P2 and Law 28/2009.